Patient and Provider Satisfaction With a Geomapping Tool for Finding Community Family Physicians in Ontario, Canada: Cross-Sectional Online Survey Study. - Belanger, Christopher; Peixoto, Cayden; Francoeur, Sara; Bjerre, Lise M. (JMIR formative research, 2024)
Background: Language-concordant health care, or health care in a patient’s language of choice, is an important element of health accessibility that improves patient safety and comfort and facilitates an increased quality of care. However, prior research has found that linguistic minorities often face higher travel burdens to access language-concordant care compared to the general population. Objective: This study intended to assess patient experiences and satisfaction with an online interactive physician map that allows patients to find family physicians who speak their preferred language in and around Ottawa, Ontario, Canada, as a means of identifying areas of improvement. Methods: This study used an online survey with questions related to user satisfaction. Responses to Likert-scale questions were compiled as summary statistics and short-answer responses underwent thematic analysis. The study setting was Ottawa and Renfrew County, Ontario, and the surrounding region, including the province of Quebec. Results: A total of 93 respondents completed the survey and self-identified as living in Ontario or Quebec. Overall, 57 (61%) respondents were “very satisfied” or “somewhat satisfied” with the map, 16 (17%) were “neither satisfied nor dissatisfied,” and 20 (22%) were “very dissatisfied” or “somewhat dissatisfied.” We found no significant differences in satisfaction by preferred language, age group, physician attachment, or intended beneficiary. A total of 56 respondents provided short-answer responses to an open-ended question about map improvements. The most common specific suggestion was to show which physicians are accepting new patients (n=20). Other suggestions included data refreshes (n=6), user interface adjustments (n=23), and additional languages (n=2). Some participants also provided positive feedback (n=5) or expressed concern with their inability to find a family physician (n=5). Several comments included multiple suggestions. Conclusions: While most patients were satisfied with the online map, a significant minority expressed dissatisfaction that the map did not show which family physicians were accepting new patients. This suggests that there may be public interest in an accessible database of which family physicians in Ontario are currently accepting new patients.

Pratique # 24 : Communauté accueillante 2.0 et Formation Les Communautés de Pratique : une démarche collaborative pour accroître l’offre de services en français (Ontario) - Benoît, Josée; Dagnogo, Djenaba Sarah; Renaud, Alexandre (2023)
fs-ref-orig: Benoît, J., Dagnogo, D.S. & Renaud, A. (2023, mise à jour 2025). Pratique # 24 : Communauté accueillante 2.0 et Formation Les Communautés de Pratique : une démarche collaborative pour accroître l’offre de services en français (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_ pratiques_novatrices.html fs-code-orig: Benoit-2025f

Évaluer le potentiel de soins linguistiquement concordants pour les francophones de l’Ontario : une étude populationnelle transversale. - Carr, Kady; Batista Moliner, Ricardo; Fitzgerald, Michael; Lamontagne, Sophie; Bader Eddeen, Anan; Timony, Patrick E.; Bédard, Daniel; Gauthier, Alain; Prud’homme, Denis; Landry, Josette-Renée; Chomienne, Marie-Hélène; Denis-Leblanc, Manon; et al. (Minorités linguistiques et société, 2024)
Cette étude a utilisé les données sur les médecins, la facturation et le recensement de 2016 dont dispose l’ICES pour examiner l’accès potentiel à des médecins de famille francophones pour les francophones résidant dans 1 643 aires de diffusion agrégées (ADA) de l’Ontario. L’Ontario compte 550 280 francophones, soit 4,1 % de sa population. Nous avons identifié 8 199 médecins de famille, parmi lesquels 1 169 se sont autodéclarés francophones. Le ratio provincial global pour les francophones était de 2,12 médecins par 1 000 résidentes et résidents, comparativement à un ratio de 0,66 pour les anglophones. Dans les ADA où les francophones étaient majoritaires, le ratio pour les francophones était inférieur au ratio pour les anglophones (0,63 vs 2,02), alors que dans toutes les autres ADA, le ratio francophone était plus élevé (3,46 vs 0,62 dans les 83,4 % des ADA où les francophones représentaient >0 % à <5 % de la population). Huit ADA du Nord-Est et de l’Est de l’Ontario présentaient un déficit relatif important de médecins de famille francophones par rapport au ratio provincial. Ces résultats donnent un aperçu des régions qui pourraient bénéficier de programmes visant à éliminer les barrières linguistiques. Mots-clés : Concordance linguistique, médecins de famille, accès aux soins primaires, francophones, Ontario

Un regard sur la distribution des médecins de famille qui parlent français dans les communautés francophones de l’Ontario - Centre de recherche en santé dans les milieux ruraux et du nord (FOCUS sur la recherche [Université Laurentienne], 2013)
site internet de Focus sur la recherche: https://fr.cranhr.ca/focus

Examining the distribution of French speaking family physicians in Ontario’s Francophone communities - Centre for Rural and Northern Health Research (FOCUS on research [Laurentian University], 2013)
site internet de Research in focus: https://www.cranhr.ca/focus

Providers of language-appropriate health care providers are scarce: Self-declared language capabilities of the healthcare workforce in Ontario - Demers, Chantal; Bourgeault, Ivy Lynn; Leal, Andrew; Simkin, Sarah; Sweetman, Arthur

Pas de problème: Rapport du comité d'action sur les services de santé en langue française, 1976 - Dubois, Jacques (Ministère de la santé, Ontario, 1976)
Ce rapport est le fruit des travaux du Comité d'action sur les services de santé en langue française, institué par le ministère de la Santé de l'Ontario et officialisé par un arrêté-en-conseil approuvé en février 1975. Le titre "Pas de problème" est choisi parce que selon le comité, il "résume assez bien la réponse des resposnables de services de santé qui n'ont pas encore perçu les besoins d'un groupe linguistique minoritaire. Pas de problème. Cette simplification d'une situation pourtant très complexe dénote sans doute l'attitude que rencontre trop souvent la population française de l'Ontario." Après une brève recension d'écrits (majoritairement américains) sur les barrières linguistiques en santé, le rapport fait un état des lieux en Ontario à cette époque et énonce plus d'une centaine de recommandations.

Active offer of health services in French in Ontario: Analysis of reorganization and management strategies of health-care organizations - Farmanova, Elina; Bonneville, Luc; Bouchard, Louise (The International Journal of Health Planning and Management, 2018)
The availability of health services in French is not only weak but also inexistent in some regions in Canada. As a result, estimated 78% of more than a million of Francophones living in a minority situation in Canada experience difficulties accessing health care in French. To promote the delivery of health services in French, publicly funded organizations are encouraged to take measures to ensure that French-language services are clearly visible, available, easily accessible, and equivalent to the quality of services offered in English. Objective This study examines the reorganization and management strategies taken by health care organizations in Ontario that provide health services in French. Methods Review and analysis of designation plans of a sample of health care organizations. Results Few health care organizations providing services in French have concrete strategies to guarantee availability, visibility, and accessibility of French-language services. Conclusions Implementation of the active offer of French-language services is likely to be difficult and slow. The Ontario government must strengthen collaboration with health care organizations, Francophone communities, and other key actors participating in the designation process to help health care organizations build capacities for the effective offer of French-language services.

Success strategies for linguistically competent healthcare: The magic bullets and cautionary tales of active offer of French-language health services in Ontario - Farmanova, Elina; Bouchard, Louise; Bonneville, Luc (Healthcare Quaterly, 2018)
An active offer of French-language health services (FLHS) was introduced in several Canadian provinces to help create an environment that will anticipate the needs of Francophones in their community and will stimulate the demand for services in French. For the active offer to be implemented, changes in how health services are organized and managed at both organizational and system levels must be introduced. In this perspective paper, we identify several success strategies and potential pitfalls with regards to the implementation of the active offer of FLHS primarily at the level of healthcare organization. Our recommendations are based on a recent health services research study exploring reorganization and management strategies for the delivery of the active offer of FLHS in Ontario and insights from a focus group with healthcare administrators conducted as part of this research. We propose a "wrap-around strategy" called organizational health literacy to help reorient organizational culture and improve management and sustainability of the active offer of FLHS. These strategies have relevance for advocates and professionals working to promote an active offer of FLHS, including healthcare administrators, human resource professionals, quality-improvement specialists and others.

Offering health services in French: Between obstacles and favourable factors in Anglophone hospital settings - Forgues, Éric; Bahi, Boniface; Michaud, Jacques (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Offre de services de santé en français : entre obstacles et facteurs favorables en milieu hospitalier anglophone - Forgues, Éric; Bahi, Boniface; Michaud, Jacques (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé Notre chapitre vise à mettre en relief les facteurs sociaux et organisationnels qui favorisent l’offre de services de santé en français par des professionnels travaillant dans des établissements de santé majoritairement anglophones. Il présente une perspective sociologique qui invite les intervenants à tenir compte de la complexité de l’environnement socio-organisationnel dans lequel pratiquent les professionnels de la santé. Ainsi, leurs compétences linguistiques ne suffisent pas à assurer pareille offre. L’engagement de la haute direction et de ses gestionnaires, la gestion des services et des ressources humaines, les relations de travail, la disponibilité de la main-d’oeuvre bilingue, le contexte juridique et politique sont, entre autres facteurs, des éléments à considérer afin de comprendre dans tous ses aspects la prestation de services de santé en français. Plus largement, ils renvoient nécessairement aux rapports sociaux qu’entretiennent les anglophones et les francophones. Mots-clés : services de santé, environnement socio-organisationnel, droits linguistiques, professionnels de la santé.
Chapitre 7

L’offre de services de santé en français en contexte francophone minoritaire - Forgues, Éric; Bahi, Boniface; Michaud, Jacques; Deveau, Kenneth; Boudreau, Jonathan; St-Onge, Sylvain (Institut canadien de recherche sur les minorités linguistiques, 2011)

Examining the geographic distribution of French-speaking physicians in Ontario - Gauthier Alain P.; Timony Patrick E.; Wenghofer, Elizabeth. F. (Canadian Family Physician, 2012)
Abstract: Objective: To determine how many physicians in Ontario express a proficiency in providing services in the French language, and to assess the geographic distribution of such physicians. Design: Population-based analysis of the 2007 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. Setting: Ontario. Participants: A total of 22688 GPs, FPs, and other specialists certified by the College of Family Physicians of Canada and the Royal College of Physicians and Surgeons of Canada who responded to the survey. Main outcome measures: First official language spoken and languages of competency to conduct practice. Results: The physician-to-patient ratio by first official language spoken is 1 physician per 138 Francophone patients in Ontario. There is 1 French-speaking GP or FP for every 297 Francophone patients, and most French-speaking physicians are located in southern Ontario (91.4%), at a ratio of 1 physician per 111 Francophone patients. The most promising French-speaking physician–to–Francophone patient ratios are found in southern Ontario (1:248 for GPs and FPs, and 1:202 for other specialists) and in urban Ontario (1:266 for GPs and FPs, and 1:209 for other specialists). Conclusion: Clearly, there is a promising number of physicians, relative to the amount of French-speaking residents in Ontario, who identified a competency in offering services in French. However, while the number of physicians who indicated a self-assessed competency to deliver health services in French is promising, it is the maldistribution of such services that is of concern. Thus, efforts must be made to attract French-speaking physicians to areas where there is the greatest demand, particularly in the northern part of the province. Résumé Objectif: Déterminer combien de médecins ontariens se disent compétents pour fournir, des services en français et vérifier la distribution géographique de ces médecins. Type d’étude: Analyse démographique du rapport de 2007 sur la réinscription annuelle à l’Ordre des médecins et chirurgiens de l’Ontario. Contexte: L’Ontario. Participants: Un total de 22 688 omnipraticiens (OP), MF et autres spécialistes diplômés du Collège des médecins de famille du Canada et du Collège royal des médecins et chirurgiens du Canada qui ont répondu à l’enquête. Principaux paramètres à l’étude: Première langue officielle parlée et langues de compétence pour la pratique. Résultats: En Ontario, le rapport médecin/patient dans le cas de la première langue officielle parlée est de 1 médecin pour 138 patients francophones. On compte un OP ou MF francophone pour 297 patients francophones et les médecins francophones sont localisés pour la plupart (91,4%) dans le sud de l’Ontario, où on observe 1 médecin pour 111 patients francophones. C’est dans le sud de l’Ontario que le rapport médecin francophone/patient francophone est le plus favorable (1/248 pour les OP et les MF, et 1/1202 pour les autres spécialistes) et dans les milieux urbains (1/266 pour les OP et les MF et 1/1209 pour les autres spécialistes). Conclusion: Il est certain qu’en Ontario, il y a un nombre encourageant de médecins qui, par rapport au nombre de résidents francophones, se sont dits compétents pour offrir des services en français. Malgré ce rapport favorable, c’est la mauvaise distribution de ces services qui est préoccupante. Il faudrait donc s’efforcer d’attirer des médecins francophones dans les régions où la demande est la plus forte, notamment dans le nord de la province.

Barriers and strategies to offering health services to French-speaking patients: Perspectives from family physicians in Northeastern Ontario - Gauthier, Alain P.; Timony, Patrick E. (Research in FOCUS on Research [Centre for rural and northern health research], 2015)
site internet de Research in focus: https://www.cranhr.ca/focus

Les obstacles et les stratégies dans les services de santé offerts aux patients francophones : perspectives des médecins de famille dans le Nord-Est de l'Ontario - Gauthier, Alain P.; Timony, Patrick E. (FOCUS sur la recherche [Centre de recherche en santé dans les milieux ruraux et du nord], 2015)
site internet de Focus sur la recherche: https://fr.cranhr.ca/focus

Affichage de postes bilingues dans la région de Kingston. Un guide utile pour les employeurs des secteurs de la santé et des services sociaux et communautaires | Job posting resource for bilingual positions in the Kingston area. A useful guide for employers in the healthcare and social community services sectors - Réseau des services de santé en français de l'Est de l'Ontario (A useful guide for employers in the healthcare and social community services sectors, 2019)

Services en français dans les CLOSM : produire des données probantes pour améliorer l’accès et la qualité. Mémoire du Réseau des services de santé en français de l’Est de l’Ontario dans le cadre de la consultation sur le renouvellement du PCLOS 2013-2018 - Réseau des services de santé en français de l’Est de l’Ontario (2016)

Préparer le terrain. Soins de santé primaires en français dans le Sud de l'Ontario. Rapport régional - Réseau franco-santé du Sud de l'Ontario (2006)

Workload of French-speaking family physicians in Francophone rural and Northern communities in Ontario - Timony, Patrick E.; Gauthier, Alain P.; Sanou, Boroma; Wenghofer, Elizabeth. F. (Canadian Journal of Rural Medicine, 2018)
Introduction: Previous studies have shown that French-speaking family physicians (FSPs) in Ontario are less numerous in areas with high proportions of francophones. The purpose of the current study was to assess whether the degree of concordance between physicians' language of competence and the linguistic profile of the community in which they practise is associated with workload and to explore variations in this relation in rural and northern regions of the province. Methods: This was a secondary analysis of the 2013 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey. We analyzed the primary practice location and language of competence of family physicians/general practitioners. We compared the practice characteristics of FSPs and non-French-speaking physicians (NFSPs) by the proportion of the francophone population, geographic location (north vs. south) and community size (urban vs. rural). Results: Data for 10 548 family physician/general practitioners were analyzed. In areas densely populated by francophones, FSPs worked more hours per week on average and had a greater mean number of patient visits than NFSPs. Non-French-speaking physicians working in areas densely populated by francophones had fewer patient visits per hour on average than FSPs. In most cases, the results were particularly accentuated in rural and northern communities. Conclusion: Our findings suggest that, compared to NFSPs, the demands placed on FSPs are disproportionately greater in communities where the need for French-language health care services is greatest and the supply of FSPs is the smallest. Our results underline the importance of properly preparing family physicians to work in areas densely populated by francophones.

Barriers to offering French language physician services in rural and Northern Ontario - Timony, Patrick E.; Gauthier, Alain P.; Serresse, Suzanne; Goodale, Natalie; Prpic, Jason (Rural and Remote Health, 2016)
Introduction: Rural and Northern Ontario francophones face many health-related challenges including poor health status, a poor supply of French-speaking physicians, and the potential for an inability or reduced ability to effectively communicate with anglophone healthcare providers. As such, it can reasonably be expected that rural and Northern Ontario francophones experience barriers when receiving care. However, the experience of physicians working in areas densely populated by francophones is largely unexplored. This paper identifies barriers experienced by French-speaking and Non-French-speaking rural and Northern Ontario physicians when serving francophone patients. Methods: A series of key informant interviews were conducted with 18 family physicians practicing in rural and urban francophone communities of Northeastern Ontario. Interviews were analyzed using a thematic analysis process. Results: Five categories of barrier were identified: (1) language discordance, (2) characteristics of francophone patients, (3) dominance of English in the medical profession, (4) lack of French-speaking medical personnel, and (5) physicians’ linguistic (in)sensitivity. Some barriers identified were unique to Non-French-speaking physicians (eg language discordance, use of interpreters, feelings of inadequacy), some were unique to French-speaking physicians (eg limited French education and resources), and some were common to both groups (eg lack of French-speaking colleagues/staff, added time commitments, and the particularities of Franco-Ontarian preferences and culture). Conclusions: Healthcare providers and decision makers may take interest in these results. Although physicians were the focus of the present article, the barriers expressed are likely experienced by other healthcare providers, and thus the lessons learned from this article extend beyond the physician workforce. Efforts must be made to offer educational opportunities for physicians and other healthcare providers working in areas densely populated by francophones; these include linguistic and cultural sensitivity training, in addition to teaching strategies for the practice of ‘active offer’ of French-language services. In sum, the present study outlines the importance of linguistic concordant communication in healthcare delivery, and describes some of the challenges faced when providing French-language services in rural and Northern Ontario. Key words: Canada, doctor–patient communication, French-language services, key informant interviews, language concordance, language discordance, Northern Ontario, Ontario francophones, physicians.

The pharmacist is in: The availability and distribution of French-speaking pharmacists in Ontario - Timony, Patrick E.; Waite, Nancy; Houle, Sherilyn; Violette, Richard; Gauthier, Alain P. (Linguistic Minorities and Society, 2022)
Francophones are an official language minority in Ontario with limited access to linguistically concordant healthcare services. Although communication is an important skill in the field of pharmacy, little is known about the availability of French-speaking pharmacists. This secondary data analysis of the Ontario College of Pharmacists registry converted weekly hours worked into full-time equivalents (FTEs) and calculated ratios of pharmacist FTEs per 1,000 population. French-speaking pharmacists tended to offer fewer FTEs in communities with a larger concentration of Francophones, particularly in northern and rural areas, a trend that was not observed among English-speaking pharmacists. This maldistribution of French-speaking pharmacists may limit the ability of official language minority patients to receive pharmacy services in their language of choice. Keywords: English, pharmacists, Francophones, linguistic concordance, geographic distribution, French-language health services

Promising quantities, disappointing distribution. Investigating the presence of French-speaking physicians in Ontario’s rural francophone communities - Timony, Patrick; Gauthier, Alain; Hogenbirk, John. C.; Wenghofer, Elizabeth (Rural and Remote Health, 2013)
Introduction: Previous studies have suggested that there may be a lack of French language healthcare services in the province of Ontario. The purpose of this study was to determine if physicians in Ontario who expressed a proficiency in providing services in the French language are located in 'Francophone communities'. Method: Responses from 10 968 Ontario-based family physicians (FPs) certified by the College of Family Physicians of Canada and uncertified general practitioners (GPs) who responded to the 2007 College of Physicians and Surgeons of Ontario Annual Membership Renewal Survey were analysed and compared to the 2006 census of the population of Ontario. Main outcome measures were the number of FP/GPs categorized by their language of competency to conduct medical practice and the number of people categorized by their first official language spoken. The physician-to-population ratio was then compared for different groups of communities in Ontario categorized by the degree of francophonie of the community: strong French communities, with a Francophone population ≥25%; moderate French communities, with a Francophone population of 10-24%; and weak/no French communities, with a Francophone population <10%. Results: There are 5.6 French speaking FP/GPs for every 1000 Francophones in communities with a French population less than 10%. This ratio is considerably greater than what was found in moderate French communities (3.4 FP/GPs) and strong French (1.3 FP/GPs). Overall the lowest ratios were found in rural strong French communities both in southern and northern Ontario (0.8 FP/GPs and 0.9 FP/GPs respectively). The ratio for all of Ontario was 0.7-1.3. Conclusions: As the number of Francophones increases in a community, the availability of French-speaking FP/GPs actually decreases, particularly in rural northern Ontario. Furthermore, there is a paradoxical relationship between the potentially high number of FP/GPs in the province with French-language capabilities and the perceived deficiencies in the availability of French language medical services. Key words: family physician, Francophone community, general practitioners, health and human resources, language, physician-patient ratios, urban. Introduction